Fractured Tracheostomy Tube - An Unusual Foreign Body in Tracheobronchial Tree - Sanu P Moideen; G Arun; M Mohan; Khizer Hussain Afroze (Bengal Journal of Otolaryngology and Head Neck Surgery, 2017)
Introduction